Multicultural Islam in the Ottoman Turkish Civilization during the Medieval Era - Abdurahman, Dudung; Maimunah, Siti; Ma'mun, Sukron; Adnani, Soraya (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The objective of this study is to explore the Ottoman Empire's management model in navigating a diverse, multiethnic, and multireligious society, thereby fostering an advanced and dynamic civilization. Employing a qualitative approach with a content analysis model during data interpretation, this research identifies a synergistic alignment between the open policy and the empire's response to ethnic, cultural, and religious differences. This alignment stems from the extensive conquest process and the organic awareness within the community, influencing social interactions. The open policy, characterized by the establishment of local entities such as readers, millets, reāyā, sipähis, and timars, facilitates the accommodation of diverse interests, worship practices, and cultural expressions. This policy is instrumental in supporting a society's multicultural awareness, fostering openness to cultural assimilation, and promoting respect for religious practices. Notably, Islam is positioned as a safeguard to ensure the enforcement of power supremacy as outlined in The Ottoman code, but the state largely refrains from intervening in religious activities and cultural expressions unless there is a clear threat to its authority. This awareness of distinct private and public spheres fosters a pluralistic and multicultural reality within Ottoman society, with the state adopting a relatively moderate position.